Upaya Meningkatkan Kemampuan Guru dalam Menyusun Tes Hasil Belajar Akhir Semester Melalui Workshop di Sekolah Binaan SD Negeri 17/III Sanggaran Agung Semester Genap Tahun Ajaran 2021/2022 - Mat Sujarti (Departement of Mathematics Education, 2022)
This study aims to obtain data/information and discuss how to improve teachers' abilities in preparing end-of-semester learning outcomes tests through workshops at target schools SD Negeri 17/III Sanggar Agung even semester 2021/2022 academic year. This type of research is School Action Research (PTS). This research was conducted at SD Negeri 17/III Sanggar Agung, Lake Kerinci District, Kerinci Regency, Jambi Province. SD Negeri 17/III Sanggar Agung is one of the schools that the author assisted in the academic year in Kerinci Regency. This research was conducted in the even semester of the 2021/2022 school year, from February to March 2022. The subjects in this study were 5 teachers at SD Negeri 17/III Sanggar Agung. The research procedure consisted of two cycles with four research stages starting from planning, implementing, observing and reflecting. Data collection techniques in this study used observation and documentation sheets. The collected data were analyzed using the percentage formula. The results of the study showed that there was an increase in the teacher's ability to prepare final semester learning outcomes tests through workshops at SD Negeri 17/III Sanggar Agung Even Semester Academic Year 2021/2022 starting from the pre-cycle, cycle I and cycle II.